The WANPRESTASI DALAM SEWA MENYEWA RUMAH DAN PERLINDUNGAN HUKUM BAGI PENYEWA RUMAH DI INDONESIA - Lumbantoruan, Zeffanya Alexander; Laksana, I Gusti Ngurah Dharma (Kertha Negara : Journal Ilmu Hukum; Vol 12 No 10 (2024), 2025)
The writing of the article aims to further analyze matters of default in house leases and legal protection for house tenants in Indonesia. In the context of Indonesian law, the definition and regulation of default can be found in the Civil Code (KUHPerdata). The relevant articles, such as Article 1233, Article 1243, Article 1244, and Article 1245 of the Civil Code, provide an overview of default and the legal consequences that may arise as a result of a breach of agreement. The type of research in this article includes normative legal research. Normative legal research is a form of legal research that involves researching library materials and secondary data. This type of research is based on the concept that law is something that is determined through legal regulations as a standard of human behavior, or philosophized as norms or rules. Lease agreement is one form of agreement in the law of engagement in which one party (the renter) defaults in the context of engagement refers to the violation of obligations that have been agreed between the parties in an agreement or contract land or building (house, shop, warehouse) used as a place of business is an important factor in running a business venture. The place of business may be owned. Default can also occur in a lease agreement referring to the violation or non-compliance of one of the parties in fulfilling its obligations in accordance with the provisions agreed upon in the agreement. This research found that legal protection for tenants is found in Article 1243 of the Civil Code. Key Words: Default, Lease, Legal Protection